2012
DOI: 10.1371/journal.pone.0032783
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Yes Associated Protein 1 Expression Reduces Cell Proliferation and Clonogenicity of Pancreatic Cancer Cells

Abstract: BackgroundThe Hippo pathway regulates organ size by inhibiting cell proliferation and promoting cell apoptosis upon its activation. The Yes Associated Protein 1 (YAP1) is a nuclear effector of the Hippo pathway that promotes cell growth as a transcription co-activator. In human cancer, the YAP1 gene was reported as amplified and over-expressed in several tumor types.MethodsImmunohistochemical staining of YAP1 protein was used to assess the expression of YAP1 in pancreatic tumor tissues. siRNA oligonucleotides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 44 publications
(50 reference statements)
7
64
0
3
Order By: Relevance
“…Consistent with reports in other cell lines (10,41), ablation of YAP in LPCs decreased cellular proliferation (Fig. 1A) in cells with undetectable YAP expression as determined by Western blot (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with reports in other cell lines (10,41), ablation of YAP in LPCs decreased cellular proliferation (Fig. 1A) in cells with undetectable YAP expression as determined by Western blot (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Overexpression of YAP1 leads to loss of contact inhibition and increases the organ size (Huang et al 2005;Camargo et al 2007). Dysregulation of YAP1 has been identified in various types of cancer (Yuan et al 2008;Liu et al 2010;Wu et al 2010;Orr et al 2011;Zhang et al 2011;Diep et al 2012). Because of its crucial function in tissue growth and tumor development, YAP1 and its regulation have been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer cells, for instance, YAP1 expression was higher in the cytoplasm than in the nucleus [3]. However, most studies observed an increase of YAP1 in the nucleus [4,9,24].…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role during carcinogenesis in many human malignancies. The components of the Hippo signaling pathway (MST1/2, WW45, LATS1/2 and MOB1) form a protein kinase complex that leads to phosphorylation of YAP1 (YES-associated protein 1), the downstream nuclear effector of the Hippo pathway [3,4,5]. YAP1 acts as an oncogene and is overexpressed in many human tumors including colon, liver, lung, ovarian, breast and prostate cancer [4,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%